Antibacterial Activity of Combination between Probiotic Milk and Mango Honey Against Streptococcus Mutans - Inaaroh Waachidah Azzulfiyyah (R.K. Sharma, Institute of Medico-Legal Publications, 2020)
Background: Streptococcus mutans commonly found in oral cavity and can be a pathogenic bacteria that leads to dental caries. Rinsing the oral cavity with antibiotic oral therapy is not suggested as the treatment of dental caries, because it has side effects. It can cause resistance of Streptococcus mutans towards antibiotic.